ORDENAMIENTO TERRITORIAL Y CONFLICTOS JURISDICCIONALES EN EL BOLÍVAR GRANDE 1800-1886 - Solano D., Sergio Paolo (Historia Caribe, 2008)
Este trabajo analiza el ordenamiento político-administrativo del espacio del Bolívar Grande a la luz de las rivalidades entre los centros urbanos emergentes y los intereses económicos y políticos de sectores sociales interesados en desglosarse del dominio de Cartagena. Esas aspiraciones autonomistas fueron controladas por las capitales regionales tradicionales en Medio de la paradójica situación del establecimiento del régimen federal. PALABRAS CLAVES Territorio, autonomía, conflictos, federalismo, centralismo. ABSTRACT This article revises the political and administrative order regarding to an approach of the entire zone of Bolivar grande based on the struggles among the emergent city areas and the economical and political concerns of social actors who showed special interest in being separative from Cartagena regime. These autonomist attempts were partially controlled by the traditional regional government involved in a paradoxical context prorogued by the stablishment of the federal regime. KEY WORD Territory, autonomy, struggles, federalism, centralism.